A RARE CASE OF COMPLETE POSTPARTUM CERVICO-UTERINE EVERSION THROUGH VAGINAL FISTULA IN A BUFFALO - KASRIJA, R; GHUMAN, S P S; GANDOTRA, V K (The Indian Journal of Animal Reproduction, 2023)
A rare case of complete eversion of cervix and uterus through vaginal fistula during postpartum period in a buffalo is reported.